The development and application of contemporary phosphorus flame retardants: a review - Yin, Zheng; Jiang, Zhiyang; Wu, Tingsen (Frontiers in Materials, 2025)
In modern society, Organophosphorus flame retardants, as a class of widely used materials, have been extensively studied and applied across various fields. The diversity and uniqueness of phosphorus flame retardant, as well as the important role of its mechanism of action in the gas phase and condensed phase, determine that it is a good flame retardant material. In addition, the article highlights the range of applications of phosphorus flame retardants in a variety of materials, including polymers, coatings, fibers, and more. At the same time, the importance and future prospects of phosphorus flame retardant research are pointed out, and the development idea of organophosphorus flame retardant is proposed through the development of phosphorus flame retardant with a new structure and the in-depth study of the properties of different aspects of phosphorus flame retardant, which can provide strong support for the development of flame retardant technology.